2004
DOI: 10.1007/s10522-004-2576-x
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes of insulin receptors, plasma insulin and glucose level

Abstract: The effects of aging on hepatic and erythrocyte insulin receptors have been investigated in 6, 12, 18 and 21-months-old compare to 3-months-old rats. Plasma insulin was elevated in 6, 12 and 18-months-old rats. Specific binding of insulin in liver was increased at the age of 8 months and accompanied with increase in concentration of low affinity binding sites, while specific binding to erythrocytes as well as concentration of both classes of binding sites was increased in 6-months-old rats. The protein and mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
3
0
1
Order By: Relevance
“…4) leading to various health problem such as diabetes, cardiovascular complications, osteoporosis and others. Veiga et al (2004) have reviewed the changes in the sex hormones and brain aging, and the authors have discussed the role of these hormones in modulating neurotransmitter synthesis, neurotransmitter receptor expression and synaptic transmission and remodeling, emphasizing that the nervous system E estrogen, P progesterone is a target for sex hormones and a source of sex steroids (Korićanac et al 2004; Table 5). The physiological variations in the concentration of sex hormones could affect the insulin receptor action and their interaction with glucose, thereby altering the carbohydrate metabolism (Valdes et al 1991).…”
Section: Aging and Effect Of Hormone Interactions Peptide And Steroidmentioning
confidence: 99%
See 1 more Smart Citation
“…4) leading to various health problem such as diabetes, cardiovascular complications, osteoporosis and others. Veiga et al (2004) have reviewed the changes in the sex hormones and brain aging, and the authors have discussed the role of these hormones in modulating neurotransmitter synthesis, neurotransmitter receptor expression and synaptic transmission and remodeling, emphasizing that the nervous system E estrogen, P progesterone is a target for sex hormones and a source of sex steroids (Korićanac et al 2004; Table 5). The physiological variations in the concentration of sex hormones could affect the insulin receptor action and their interaction with glucose, thereby altering the carbohydrate metabolism (Valdes et al 1991).…”
Section: Aging and Effect Of Hormone Interactions Peptide And Steroidmentioning
confidence: 99%
“…Morever, the brain insulin/IR signal transduction, beside the regulation of glucose metabolism, delivers signals necessary for synaptic activity and plasticity, of memory formation and for memory storage as well as for cell differentiation (Kremerskothen et al 2002). Recently insulin levels have been measured in aging and show a decrease with age (Korićanac et al 2004), insulin levels are also decreased in DM as well as experimental diabetes in animal models (Fulop et al 2003;Biessels et al 2002b;Taha et al, unpublished).…”
Section: Changes In Neuronal Markers Diabetes Agingmentioning
confidence: 99%
“…Tikus mulai mengalami peningkatan kadar glukosa darah setelah memasuki usia 12 minggu. 21 Peningkatan usia akan berpengaruh terhadap fungsi organ, salah satunya adalah sel beta pankreas. Sel beta pankreas semakin lama akan mengalami degradasi sehingga dapat menyebabkan penurunan hormon insulin yang dihasilkan.…”
Section: Pembahasanunclassified
“…Although insulin participates in regulation of hepatic gluconeogenesis, the role which changes in hepatic insulin receptor (IR) play in genesis of age-related insulin resistance is contraversial (Fulop et al 2003). Korićanac et al (2004) demonstrated no decrease in specific binding of insulin in liver and erythrocytes, or the concentration of binding sites in both tissues during aging. However, the increase in insulinemia, elevated plasma glucose level and NO level, as well as the decrease of hepatic receptor protein and mRNA content in the oldest rats, indicate some age-related changes in insulin signaling.…”
Section: Changes In Hormone Signaling With Agingmentioning
confidence: 99%